(untitled) (Fiep Bulletin - online, 2014)
This article presents a methodological proposal, that seeks auxiliary in the treatment of the chronicle sportiv as a privileged literary source to notice the present feelings in an of-finished social moment. To reach this objective, one worked with the entitled chronicle: " Complex of Tykes ", of playwright’s Nelson Rodrigues authorship. She came a theoretical picture, that can subsidize the analysis of this document type. This picture was created taking itself in consideration that is basic to respect the moment of the literary production; who produced her; to who is destined and if something significant it was omitted. One understands each other that the wealth feels analysis type it is in the process tense servant among the present indetermination in the soccer, the freedom of the author’s of the chronicle creation and the flexibility of the established truth concept for the New Cultural History. It was noticed that is possible to analyze through this documentation type several of the present dilemmas in our society and that the soccer is an object that makes possible the determination of present singularities in the Brazilian culture, in other words, it assisted in the definition of the one that is be Brazilian, transforming the identity in something concrete, and disclosing for the world the virtues of your people, that were expressed through the players of the Brazilian Selection.